Lesbian Activism in the (Post-)Yugoslav Space Sisterhood and Unity - Bilić, Bojan; Radoman, Marija (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book intertwines academic and activist voices to engage with more than three decades of lesbian activism in the Yugoslav space. The empirically rich contributions uncover a range of lesbian initiatives and the fundamental, but rarely acknowledged, role that lesbian alliances have played in articulating a feminist response to the upsurge of nationalism, widespread violence against women, and high levels of lesbophobia and homophobia in all of the post-Yugoslav states. By offering a distinctly intergenerational and transnational perspective, this collection does not only shed new light on a severely marginalised group of people, but constitutes a pioneering effort in accounting for the intricacies - solidarities, joys, and tensions - of lesbian activist organising in a post-conflict and post-socialist environment. With a plethora of authorial standpoints and innovative methodological approaches, the volume challenges the systematic absence of (post-)Yugoslav lesbian activist enterprises from recent social science scholarship. Lesbian Activism in the (Post-)Yugoslav Space will be of interest to students and scholars across a range of disciplines, including gender studies, history, politics, anthropology, and sociology. .